2005
DOI: 10.1111/j.1445-5994.2006.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Providing guidelines and education is not enough: an audit of gentamicin use at The Royal Melbourne Hospital

Abstract: Aminoglycoside prescribing practices at our hospital are suboptimal, despite ready access to prescribing guidelines. Provision of a guideline and education sessions with doctors do not necessarily lead to widespread adoption of recommended practices. We suggest that changes to hospital systems related to prescribing and monitoring of aminoglycosides are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
(31 reference statements)
3
33
0
Order By: Relevance
“…18 In a Melbourne hospital, even after promotion of gentamicin guidelines, only 30.3% of first doses were consistent with the guidelines. 19 In our study, patients who were not weighed experienced a significant increase (v 2 = 4.94, d.f. = 1, P = 0.03) in haemorrhagic complications with therapeutic anticoagulation.…”
Section: Number Of Subjectsmentioning
confidence: 94%
“…18 In a Melbourne hospital, even after promotion of gentamicin guidelines, only 30.3% of first doses were consistent with the guidelines. 19 In our study, patients who were not weighed experienced a significant increase (v 2 = 4.94, d.f. = 1, P = 0.03) in haemorrhagic complications with therapeutic anticoagulation.…”
Section: Number Of Subjectsmentioning
confidence: 94%
“…European guidelines on the diagnosis and treatment of infective endocarditis were updated in October 2009 [4], and were in accordance with US guidelines regarding aminoglycoside use [5]. Studies in hospitals have shown that adherence to gentamicin prescribing guidelines is low [11,12]; in one study, 66% of the initial gentamicin dosings were not consistent with hospital guidelines [12]. In another hospital-based study, the use of a gentamicin monitoring form improved the proportion of appropriate starting doses from 65% to 90% [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, only 58.7% of vancomycin use was in line with local guidance for dose, dose frequency and TDM measures in a Dutch intensive care unit,12 while 34% of initial gentamicin dosing was concordant with Australian hospital guidelines 9. No previous studies have examined barriers to the appropriate use of TDM for gentamicin and vancomycin although it has been suggested that merely providing guidelines and education is not sufficient to ensure compliance,9 and that further, multidisciplinary, research into the implementation of antimicrobial guidelines is needed 14…”
Section: Introductionmentioning
confidence: 99%